Use of essential oil of Tagetes minuta L. as a guinea pig preservative - Culqui Arce, Carlos Alexánder (2020)
Essential oils are volatile compounds extracted from plants of great importance in the pharmaceutical, food and perfume industries. The research aimed to assess the shelf life of guinea pig meat vacuum packed using Tagetes minuta L. essential oil (AETm). An experimental design ofincreasing stimulus was used, in which three doses of aqueous solution of AE (0.25, 0.30 and 0.35% v / v) were applied, with four replicates and six evaluations were performed in 25 days (O; 3; 6; 14; 18 and 25) storage at 3 º C. The shelf life was determined by microbial load (Escherichia coli and Staphylococus aureus) over time, fat oxidation and pH in 26 g of guinea pig meat. The most probable number (NMP) technique was used to determine the microbial content and the lipid oxidation was determined by Rancimat as the induction time. At 14 days, all samples maintained their characteristics to be consumed; In addition, it was observed that for the inhibition of E. coli none of the concentrations had any difference, however, for S. aureus the concentration of 0.35% had a greater inhibitory effect. Therefore, it is concluded that the AETm can extend the shelflife of guinea pig meat vacuum packed for up to 14 days.